2010
DOI: 10.1186/1471-2458-10-762
|View full text |Cite
|
Sign up to set email alerts
|

Distance decay in delivery care utilisation associated with neonatal mortality. A case referent study in northern Vietnam

Abstract: BackgroundEfforts to reduce neonatal mortality are essential if the Millennium Development Goal (MDG) 4 is to be met. The impact of spatial dimensions of neonatal survival has not been thoroughly investigated even though access to good quality delivery care is considered to be one of the main priorities when trying to reduce neonatal mortality. This study examined the association between distance from the mother's home to the closest health facility and neonatal mortality, and investigated the influence of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 31 publications
4
83
0
2
Order By: Relevance
“…Although the data used in our study are a bit dated, the DHS Vietnam 2002 is still considered the most recent survey with rich and nationally representative information on prenatal care utilization, region differences, and ethnicity measurement as compared to other regional surveys (Trinh, Dibley, and Byles 2006;Målqvist et al 2010;Tran et al 2011). As other scholars of ethnic disparities in Vietnam have noted, the gap between the majority and minority populations is deeply rooted and is not likely to shrink in a short period of time ( Van de Walle and Gunewardena 2001;Salemink 2003;Baulch et al 2007;Baulch 2010;Friederichsen and Neef 2010;Imai, Gaiha, and Kang 2011;Baulch, Pham, and Reilly 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the data used in our study are a bit dated, the DHS Vietnam 2002 is still considered the most recent survey with rich and nationally representative information on prenatal care utilization, region differences, and ethnicity measurement as compared to other regional surveys (Trinh, Dibley, and Byles 2006;Målqvist et al 2010;Tran et al 2011). As other scholars of ethnic disparities in Vietnam have noted, the gap between the majority and minority populations is deeply rooted and is not likely to shrink in a short period of time ( Van de Walle and Gunewardena 2001;Salemink 2003;Baulch et al 2007;Baulch 2010;Friederichsen and Neef 2010;Imai, Gaiha, and Kang 2011;Baulch, Pham, and Reilly 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…These results are consistent with previous studies on ethnic disparities in women and child health in Vietnam. Although the government has dedicated significant effort towards implementing health care programs for pregnant women and equalizing health care (Trinh, Dibley, and Byles 2007), ethnic disparities still persist which indicated that ethnic minority women and children are at high risks of adverse health outcomes due to inadequate professional care (Målqvist et al 2010;Trinh, Dibley, and Byles 2006;Tran et al 2011). This significant disparity by ethnicity maintains when controlling for maternal demographic, socioeconomic, and community-level covariates, suggesting that while ethnic minority women are disadvantaged on several levels, such as wealth, remoteness from modern services, and early and frequent childbearing, their lower prenatal care utilization is rooted in other, unmeasured socioeconomic, and cultural factors relative to majority populations.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Following Acton (1975), several studies have confirmed the importance of distance to health care facilities in modulating demand for care, regardless of the nature of the care and of the development of the country or its Health System (Haynes et al, 1999;Jordan et al, 2004;Friedman et al, 2013;Alegana et al, 2012;Malqvist et al, 2010). This phenomenon is known as "the distance decay effect", as demand for health care decreases as distance to health care institutions increases.…”
Section: Introductionmentioning
confidence: 98%
“…A continuum of good healthcare for all pregnant and delivering women and their children is needed to cope with perinatal health problems and prevent deaths 11, 12. Examples from other countries illustrate the difficulties in reducing the number of deaths during the first month of life in comparison to postneonatal health problems.…”
Section: Child Survival Patternsmentioning
confidence: 99%